2022
DOI: 10.3390/s22176600
|View full text |Cite
|
Sign up to set email alerts
|

Wearable-Based Stair Climb Power Estimation and Activity Classification

Abstract: Stair climb power (SCP) is a clinical measure of leg muscular function assessed in-clinic via the Stair Climb Power Test (SCPT). This method is subject to human error and cannot provide continuous remote monitoring. Continuous monitoring using wearable sensors may provide a more comprehensive assessment of lower-limb muscular function. In this work, we propose an algorithm to classify stair climbing periods and estimate SCP from a lower-back worn accelerometer, which strongly agrees with the clinical standard … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…However, the applicability of these methodologies in clinical settings is limited due to practical reasons (e.g., high cost, the need of trained personnel, low transferability) 8 . Considering their accessibility and rapid advancements, wearable sensors and smartphones offer a promising avenue to measure power production during functional activities, such as chair rising 9–12 and stair‐climbing (SC) 9,13,14 . While monitoring of sit‐to‐stand performance is receiving most attention, SC is one of the elementary movements to maintain independence in public and home environments 15,16 and therefore a crucial activity to monitor in older adults.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the applicability of these methodologies in clinical settings is limited due to practical reasons (e.g., high cost, the need of trained personnel, low transferability) 8 . Considering their accessibility and rapid advancements, wearable sensors and smartphones offer a promising avenue to measure power production during functional activities, such as chair rising 9–12 and stair‐climbing (SC) 9,13,14 . While monitoring of sit‐to‐stand performance is receiving most attention, SC is one of the elementary movements to maintain independence in public and home environments 15,16 and therefore a crucial activity to monitor in older adults.…”
Section: Introductionmentioning
confidence: 99%
“…8 Considering their accessibility and rapid advancements, wearable sensors and smartphones offer a promising avenue to measure power production during functional activities, such as chair rising [9][10][11][12] and stair-climbing (SC). 9,13,14 While monitoring of sit-to-stand performance is receiving most attention, SC is one of the elementary movements to maintain independence in public and home environments 15,16 and therefore a crucial activity to monitor in older adults. Previous research demonstrated that SC power can be estimated using a single lumbar-worn sensor, 9 and that it is highly related to a "gold standard" methodology for measuring lower-limb muscle power (i.e., an isokinetic dynamometer).…”
mentioning
confidence: 99%
“…Kinematic data can be collected by means of body-fixed sensors, providing data on power production during every step of a stair [ 15 , 20 ]. We have previously demonstrated that sensor-based SC power is highly related (r = 0.80) to leg-extensor power in a group of young, middle-aged and older adults [ 15 ].…”
Section: Introductionmentioning
confidence: 99%